What causes obesity? And why has it grown so much? An alternative view - John F. Tomer (Max Planck Institute of Economics, 2010)
The purpose of this paper is to explain the main social and economic facts concerning obesity in a way that substantially improves upon existing economic theory. In contrast to existing theory, a number of recent health science writers have explained persuasively that weight gain or loss is not strictly determined by net calorie consumption. These writers have explained that what food people eat and the effect these foods have on hormones such as insulin and hormonal balance are the crucial factors. To understand the rising prevalence of obesity, it is necessary to take into account the growing infrastructure of obesity. This infrastructure includes food processing firms, notably their behavior relating to the qualities of processed food, their marketing of 'junk food' and fast food, and their food cost reducing technological changes. Another factor in rising obesity levels are the human capital resources of people, most notably their social capital, personal capital, and health capital. There is evidence that people who are poor in these intangible capacities are the ones with the highest rates of obesity. The essence of the theory is that obesity is the expected result when vulnerable people with low intangible capital resources encounter the many influences of the infrastructure of obesity. These people have gotten stuck in dysfunctional eating and exercise patterns which societal influences have unfortunately encouraged.
urn:nbn:de:gbv:27-20110628-140859-7
Keywords: 330; Körpergewicht; Verhaltensökonomik; Beschränkte Rationalität; Ernährungsverhalten; Konsumgesellschaft; Theorie; USA